2016
DOI: 10.1007/s11427-015-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Significant variations in alternative splicing patterns and expression profiles between human-mouse orthologs in early embryos

Abstract: Human and mouse orthologs are expected to have similar biological functions; however, many discrepancies have also been reported. We systematically compared human and mouse orthologs in terms of alternative splicing patterns and expression profiles. Human-mouse orthologs are divergent in alternative splicing, as human orthologs could generally encode more isoforms than their mouse orthologs. In early embryos, exon skipping is far more common with human orthologs, whereas constitutive exons are more prevalent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Mouse model results indicate that the deficiency or abnormality of type V collagen leads to a lack of fibril formation in mouse embryonic tissue and even death in the stage of early embryos (Wenstrup et al, 2004; Connizzo et al, 2015), which is similar to the phenotypes in human OI type II (perinatal lethal type). Evidences in MGI shows that mice with COL5A2 mutation present abnormal cardiovascular system physiology, abnormal skeleton development, abnormal cutaneous collagen fibril morphology, abnormal cornea morphology, embryonic lethality during organogenesis, neonatal lethality, respiratory distress, thin dermal layer, and other phenotypes (Chen et al, 2017), most of these phenotypes are very similar to the human phenotypes of OI, therefore, we suggest that the COL5A2 gene is tightly correlated with OI, especially OI type II.…”
Section: Discussionmentioning
confidence: 53%
“…Mouse model results indicate that the deficiency or abnormality of type V collagen leads to a lack of fibril formation in mouse embryonic tissue and even death in the stage of early embryos (Wenstrup et al, 2004; Connizzo et al, 2015), which is similar to the phenotypes in human OI type II (perinatal lethal type). Evidences in MGI shows that mice with COL5A2 mutation present abnormal cardiovascular system physiology, abnormal skeleton development, abnormal cutaneous collagen fibril morphology, abnormal cornea morphology, embryonic lethality during organogenesis, neonatal lethality, respiratory distress, thin dermal layer, and other phenotypes (Chen et al, 2017), most of these phenotypes are very similar to the human phenotypes of OI, therefore, we suggest that the COL5A2 gene is tightly correlated with OI, especially OI type II.…”
Section: Discussionmentioning
confidence: 53%
“…Five basic modes are generally recognized for AS, including exon-skipping (cassette exon), mutually exclusive exons, alternative donor site, alternative acceptor site, and intron retention. Lots of studies have shown that AS is very common in mammalians and over 90% of human genes could undergo AS based on bulk RNA-seq data (Wang et al, 2008; Chen et al, 2017a). Moreover, AS play crucial roles in a variety of biological processes and abnormal AS may be correlated with cancers (Sveen et al, 2016).…”
Section: Alternative Splicing and Rna Editing Analysis Of Scrna-seq Datamentioning
confidence: 99%
“…Gene regulatory network inference has been widely conducted in numerous bulk RNA-seq studies, while scRNA-seq also provides great potential for such analysis. For bulk RNA-seq data, networks are usually constructed from a number of samples using the tools like weighted gene co-expression network analysis (WGCNA) (Langfelder and Horvath, 2008; Chen et al, 2017a). A basic assumption is that the genes highly correlated in expression could be co-regulated.…”
Section: Gene Regulatory Network Reconstructionmentioning
confidence: 99%
“…Increased alternative splicing has contributed to extensive proteomic diversity in mammals, and especially primates, relative to other clades (Barbosa-Morais et al ., 2012; Gueroussov et al ., 2017). For example, exon skipping is more common in human embryos compared to mouse, contributing to approximately double the number of isoforms generated per orthologous gene (Chen et al ., 2017).…”
Section: Evolution Of Developmental Processesmentioning
confidence: 99%